A rapid field detection system for citrus huanglongbing associated 'Candidatus Liberibacter asiaticus' from the psyllid vector, Diaphorina citri Kuwayama and its implications in disease management. (February 2015) - Keremane, Manjunath L.; Ramadugu, Chandrika; Rodriguez, Esteban; Kubota, Ryo; Shibata, Scott; Hall, David G.; Roose, Mikeal L.; Jenkins, Daniel; Lee, Richard F.
Abstract: ' Candidatus Liberibacter asiaticus' (Las), associated with citrus huanglongbing (HLB or citrus greening) is spread by Diaphorina citri Kuwayama, the Asian citrus psyllid. Psyllids can be tested to assess the prevalence of Las in a population and for early detection of HLB in new areas being invaded by the psyllid. In some cases, large numbers of psyllids may need to be tested, thus there is a need for rapid and inexpensive field detection methodology. We report here on the development of a field detection kit for testing psyllids for Las using loop-mediated amplification technology (LAMP). Six samples with pools of 1–10 psyllids plus a positive and negative control can be tested at a time in about 30 min; 10 min for crude extraction and 20 min for target DNA amplification. The LAMP assays are conducted in a Smart-DART™ detection unit which is operated from an Android device. The LAMP detection method for Las is about 100 times more sensitive than the traditional real time PCR method. In addition to field testing of psyllids for Las, the methodology was validated as effective for identifying Las in plant DNA extractions. In California, where the psyllid has only recently invaded, participation of a large number of growers and extension workers in field detection may facilitate rapid containment efforts should Las be found. In areas where the disease epidemic is already in the initial stages, large scale testing can be helpful for effective disease management. The LAMP technology lends itself well in such situations. Highlights: Long latency period of citrus HLB in plants makes disease management challenging. Portable, affordable, sensitive, rapid method to detect Liberibacter in psyllids. Smart-DART™ unit connected to an Android device for a 30 min Liberibacter test. Better management of groves and use of precious resources in high priority areas. Results from users need to be reported to regulators and verified in a laboratory.